A non-interpenetrating lead-organic framework with large channels based on 1D tube-shaped SBUs. Issue 42 (8th May 2017) - Dai, Fangna; Fan, Weidong; Yuan, Xue; Huang, Zhaodi; Wang, Yutong; Xin, Xuelian; Lin, Huan; Zhang, Liangliang; Wang, Rongming; Sun, Daofeng
Abstract : A 3D open MOF based on 1D infinite tube-shaped SBUs shows efficient adsorption of I2 and selective adsorption of some dyes containing the SO3 − group. Abstract : This work presents the construction of a porous lead-organic framework (UPC-10 ) with large channels of ∼24 Å.UPC-10 shows efficient adsorption of I2 and selective adsorption of some dyes containing the SO3 − group. After the adsorption of dyes, UPC-10 exhibits a CO2 gas uptake ability. Furthermore, UPC-10 could be transformed into PbS in a H2 S atmosphere, and the derived PbS manifests N2 and CO2 uptake abilities.